Dataset associated with "Temporal variability largely explains difference in top-down and bottom-up estimates of methane emissions from a natural gas production region" - Vaughn, Timothy L.; Bell, Clay S.; Pickering, Cody, K.; Schwietzke, Stefan; Heath, Garvin, A.; Petron, Gabrielle; Zimmerle, Daniel; Schnell, Russell, C.; Nummedal, Dag (Colorado State University. Libraries, 2018)
This study is the first to spatially and temporally align top-down and bottom-up methane emission estimates for a natural gas production basin, using multi-scale emission measurements and detailed activity data reporting. We show that episodic venting from manual liquid unloadings, which occur at a small fraction of natural gas well pads, drives a factor-of-two temporal variation in the basin-scale emission rate of a US dry shale gas play. The mid-afternoon peak emission rate aligns with the sampling time of all regional aircraft emission studies, which target well-mixed boundary layer conditions present in the afternoon. A mechanistic understanding of emission estimates derived from various methods is critical for unbiased emission verification and effective GHG emission mitigation. Our results demonstrate that direct comparison of emission estimates from methods covering widely different time scales can be misleading.
This dataset includes input and output data used in the bottom-up model described in the associated manuscript and accompanying Supplemental Information Appendix. Additionally, the input dataset includes a ReadMe.txt describing it, and each of the output datasets includes a ReadMe.txt and a FileListing.txt describing their contents.
Department of Mechanical Engineering
Energy Institute
Keywords: natural gas; methane emissions; top-down; bottom-up; spatiotemporal inventory model